“A social-ecological systems approach to sustainable production of endemic rooibos (Aspalathus linearis) and honeybush (Cyclopia spp.) species amongst agrarian communities in the Cape Floristic Region (CFR)” - Malgas, Rhoda Ronette (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhDConsEcol)--Stellenbosch University, 2022.